In any ΔABC, prove that


In any ΔABC, prove that

$\frac{\sin (A-B)}{\sin (A+B)}=\frac{\left(a^{2}-b^{2}\right)}{c^{2}}$



Need to prove: $\frac{\sin (A-B)}{\sin (A+B)}=\frac{\left(a^{2}-b^{2}\right)}{c^{2}}$

We know that, $\frac{a}{\sin A}=\frac{b}{\sin B}=\frac{c}{\sin C}=2 R$ where $R$ is the circumradius.


$a=2 R \sin A \cdots(a)$

Similarly, b = 2R sinB and c = 2R sinC

From Right hand side,


$=\frac{4 R^{2} \sin ^{2} A-4 R^{2} \sin ^{2} B}{4 R^{2} \sin ^{2} C}$

$=\frac{4 R 2\left(\sin ^{2} A-\sin ^{2} B\right)}{4 R^{2} \sin ^{2} C}$

$=\frac{\sin (A+B) \sin (A-B)}{\sin ^{2} C}$

$=\frac{\sin (A+B) \sin (A-B)}{\sin ^{2}(\pi-(A+B))}$

$=\frac{\sin (A+B) \sin (A-B)}{\sin ^{2}(A+B)}$

$=\frac{\sin (A-B)}{\sin (A+B)}$

$=$ Left hand side. [Proved]


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now